Cold atmospheric plasma increases IBRV titer in MDBK cells by orchestrating the host cell network - Yujie Miao; Peiyu Han; Dong Hua; Renwu Zhou; Zhengbing Guan; Qing Lv; Xiaofeng Dai (Virulence, 2021)
Enhancing virus multiplication could assist in the rapid production of vaccines against viral diseases. Cold atmospheric plasma (CAP), a physical approach relying on reactive oxygen species to achieve the desirable cellular outcome, was shown to be effective in enhancing virus propagation, where bovine rhinotrachieitis virus and Madin-Darby Bovine Kidney cells were used as the modeling virus and cell line, respectively. CAP was shown to create synergies with virus infection in arresting host cells at the G2/M stage, decreasing cell membrane potential, increasing intracellular calcium level, and inducing selective autophagy. In addition, CAP was demonstrated to suppress virus-triggered immunogenic signaling as evaluated by IRF7 expression. We presented evidences on CAP-triggered maximization of host resources toward virus multiplication that is advantageous for viral vaccine production, and opened a novel regime for applying CAP in the sector of medical care and health.